Interpersonal skill dan penyelesaian konflik individu pada usia dewasa awal - Preysi Sherly Siby; Lilies Sri Rachmawati Joesoef (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to determine the effect of interpersonal skills on conflict resolution. The hypothesis in this study is that there is an influence between interpersonal skills on individual conflict resolution in early adulthood. This research uses quantitative research methods. The subjects used were the population of early adulthood in Neighborhood II, Malalayang Dua Village, Malalayang District, Manado City with a total of 80 people. The data analysis technique used in this research is simple linear regression and product moment correlation technique using manual calculations and the help of a computer program, namely SPSS. Based on the results of data analysis, the regression equation = 14.738 + 0.779 X, with the results of t arithmetic = 8.302 > t table = 1.9908, so Ho is rejected and Ha is accepted. So it can be concluded that interpersonal skills have an influence on conflict resolution. Keywords: Interpersonal Skills; Conflict; Conflict Resolution.